Efficacy of Dexmedetomidine Combined with Bupivacaine in Supraclavicular Block Versus Bupivacaine alone in Upper Limb Surgery - Ahmed, Maira; Hussain, Akhtar; Majeed, Kaukab; Akhter, Amim; Qureshi, Sajjad; Ahsin, Arooj (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy of Dexmedetomidine combined with Bupivacaine in supraclavicular block versus Bupivacaine alone in upper limb surgeries Study Design: Quasi-experimental study Place and Duration Of Study: Anaesthesia Department, Combined Military Hospital Quetta, Pakistan, from Sep to Feb 2022. Methodology: Patients planning to undergo plating of radius fractures were included. The patients were divided into two equal sets (n=20) by purposive sampling and marked as Group-A and Group-B. Patients in both groups received supraclavicular block under ultrasound guidance and general endotracheal anaesthesia followed by that. In the first Group,Bupivacaine plain (0.125%) was used to block the brachial plexus, and in the second Group, Bupivacaine (0.125%) with adjuvant Dexmedetomidine (1ug/kg) was given respectively. The visual analogue scale was used to measure pain perception in both groups. Results: The duration of analgesia in the Dexmedetomidine Group was 10 ±0.925 hours and 5.68 ±0.471hours in Bupivacaine Group, which holds statistical significance (p-value<0.001). The demographics, surgery-related parameters (duration and type of surgery), block related parameters (onset of block and time taken to block) were similar in both study groups. Conclusion: We concluded that Dexmedetomidine prolongs the duration of analgesia significantly when used as an adjuvant Bupivacaine in supraclavicular brachial plexus block.